Application of the hybrid-type method of Brownian dynamics and lattice Boltzmann to magnetic particle suspensions - Akira SATOH (The Japan Society of Mechanical Engineers, 2015)
We have investigated the feasibility of the hybrid-type method of lattice Boltzmann and Brownian dynamics as a simulation technique for a magnetic particle suspension. To do so, we have addressed aggregation phenomena in thermodynamic equilibrium and have compared the present results with those of Monte Carlo method and the previous lattice Boltzmann method based on fluctuation hydrodynamics (FH). The viscosity-modifying technique has been employed for sophisticating the activation level of the translational and rotational Brownian motion of magnetic particles. From the results regarding the snapshots and pair correlation functions, the present hybrid-type simulation method is seen to show good agreement with the results of Monte Carlo and FH-based lattice Boltzmann method both quantitatively and qualitatively. For example, the characteristics of the magnetization are in good agreement with Monte Carlo and FH-based lattice Boltzmann results. This clearly shows that the rotational Brownian motion of magnetic particles is activated at a physically reasonable level.